2015
DOI: 10.1021/nn5060442
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Microsupercapacitors Based on Two-Dimensional Graphene/Manganese Dioxide/Silver Nanowire Ternary Hybrid Film

Abstract: Microsupercapacitors (MSCs), as one type of significant power source or energy storage unit in microelectronic devices, have attracted more and more attention. However, how to reasonably design electrode structures and exploit the active materials to endow the MSCs with excellent performances in a limited surface area still remains a challenge. Here, a reduced graphene oxide (RGO)/manganese dioxide (MnO2)/silver nanowire (AgNW) ternary hybrid film (RGMA ternary hybrid film) is successfully fabricated by a faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
159
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(168 citation statements)
references
References 68 publications
7
159
1
1
Order By: Relevance
“…Recent demand of thin and light micro-supercapacitors for portable electronic devices has made supercapacitors a popular type of power source and energy storage unit [7][8][9][10][11][12][13][14]. Carbonaceous materials, such as activated carbon, carbon nanotubes (CNTs) and graphene, are important and essential electrode materials for use in micro-supercapacitors [2].…”
Section: Introductionmentioning
confidence: 99%
“…Recent demand of thin and light micro-supercapacitors for portable electronic devices has made supercapacitors a popular type of power source and energy storage unit [7][8][9][10][11][12][13][14]. Carbonaceous materials, such as activated carbon, carbon nanotubes (CNTs) and graphene, are important and essential electrode materials for use in micro-supercapacitors [2].…”
Section: Introductionmentioning
confidence: 99%
“…This is probably due to a higher salt concentration in the electrolyte as the result of gel drying. A stack capacitance up to 99.1 F cm −3 , corresponding to an energy density of 6.74 mW h cm −3 , has been obtained from the solid‐state hierarchical NPG/MnO 2 MPCs with a MnO 2 plating time of 11 min (Figure 4b), which is much higher than the literature values of the best carbon/graphene‐based MSCs (1.3 F cm −3 for onion‐like carbon based MSCs,2 3.1 F cm −3 for laser‐written reduced graphene oxide MSCs,8 3.05 F cm −3 for laser‐scribed graphene MSCs,9 17.9 F cm −3 for reduced graphene MSCs10 and 6.1 F cm −3 for reduced graphene oxide/carbon nanotube MSCs12) and pseudocapacitive microdevices (16.4–39.3 F cm −3 for MnO x /Au multilayer MSCs,19 26.5–66.0 F cm −3 for polyaniline nanowire array MSCs,17 8–25 F cm −3 for CoO/carbon nanotube MSCs,39 4.42 F cm −3 for graphene/MnO 2 /Ag nanowire MSCs40 and 30–50 F cm −3 for MWCNT/MnO x MSCs41) (Table S2, Supporting Information). Even at a high current density of 0.5 mA cm −2 (0.5 mA cm −2 corresponds to about 18.4 A g −1 MnO2 for 7 min plating, and 13.2 A g −1 MnO2 for 11 min plating), the stack capacitance is as high as 61.5 F cm −3 (Figure 4b).…”
mentioning
confidence: 99%
“…As a result, the use of Ag NWs as STECs for supercapacitors has been constrained and they have only been used as supporters or auxiliary conductors. [190][191][192][193][194] Recently, Lee et al reported that the stability of Ag NWs can be enhanced by conformal coating of the Au thin layer as shown in Figure 11b. [85] The Ag-Au NW electrode presented enhanced air/electrochemical stability (Figure 11c), and the resistance increased 2.6 times at 30% strain.…”
Section: Supercapacitorsmentioning
confidence: 99%